User-Centered Design Method in the Analysis of User Interface Design of the Department of Informatics System’s Website - Melda Agarina; Arman Suryadi Karim; Sutedi Sutedi (Proceeding International Conference on Information Technology and Business, 2019)
The user interface is a fundamental aspect of building a website. A proper analysis of user the interface design system will have a profound impact on the actual use of a website. Many cases of website building result in minimal usability and low traffic. The purpose of this study is to analyze the user interface design of the Department of Informatics System’s website. The website mainly serves as an information portal for students in the department. It also provides features that students can access to assist them in either academic or nonacademic activities and improve the general effectiveness and quality of the department. User-centered design (UCD) method is used as the basis of the present analysis. At UCD, theprocess of user interface design engages the users to provide feedback or evaluation via a questionnaire for improving a website’s interface, accessibility, and usefulness. The analysis on the Department of Informatics System’s website shows that its interface design and usability have generally been satisfactory despite several shortcomings, which need quality improvement and further developmentKeywords: user interface, UCD, website